Residue Management Methods in Wheat Cultivation: A Feasibility Analysis: FEASIBILITY STUDY OF RESIDUE MANAGEMENT IN WHEAT - Abhishek Upadhyay, Abhishek Upadhyay; R. K. Naik, R. K. Naik; Gautam, Prem Veer; Arshad Quraishi, Arshad Quraishi (Annals of Arid Zone, 2024)
Paddy residues are vital natural resources, and their reuse can significantly improve the physical, chemical, and organic properties of soils, leading to increased crop production. Managing crop residues presents a significant challenge to combine-harvested paddy fields within the rice wheat cultivation system, which is predominantly employed in the Indian subcontinent. This study aims to present the performance evaluation of three sowing methods for wheat in the field after combine harvested paddy crop. The study was conducted at the Instructional Farm of Farm Machinery and Power Engineering Department, Swami Vivekanand College of Agricultural Engineering Technology and Research Station, Raipur, Chhattisgarh, India with three sowing methods such as the combination of a rotary mulcher with a zero-till seed cum fertilizer-drill (M1), zero-till seed cum fertilizer-drill (M2), and turbo happy seeder (M3). The field efficiency of tractor-operated implements such as a rotary mulcher, zero-till seed cum fertilizer drill, and turbo happy seeder was measured as 66.1, 69.96, and 70.51%, respectively. The M3 sowing method was the most effective in reducing straw length by 71.02% and incorporating straw into the soil by 51.66%. M1 had a moderate reduction in straw length (41.50%) and a low incorporation rate of 7.37%. In contrast, the M2 method showed the least impact, with no reduction in straw length or soil incorporation. The operating costs per hectare for M3 (Rs. 2099) were significantly lower than those for M2 (Rs. 2300) and M1 (Rs. 3541) because there was less fuel consumption for the operation. So, the turbo happy seeder or M3 method outperformed M1 and M2 in residue and biometric parameters, plus economic analysis. Therefore, M3 can be recommended to use on farmers’ fields for rice residue management after combine harvesting to boost soil health and crop yield.